Brokerage roles in disaster response: organisational mediation in the wake of Hurricane Katrina. (18th August 2008) - Lind, Benjamin E.; Tirado, Miguel; Butts, Carter T.; Petrescu-Prahova, Miruna
When one organisation serves as an intermediary for two other organisations which are not in direct contact, that organisation is said to engage in brokerage behaviour. Using the case of the Hurricane Katrina disaster, this study demonstrates the use of formal brokerage measures to study communication among the responding organisations. We apply the brokerage role typology put forth by Gould and Fernandez (1989) to communication networks among the responding organisations in two communities: Saint Bernard Parish, Louisiana and Bay Saint Louis, Mississippi. We find that relatively few organisations perform most of the brokerage; primarily, these brokering organisations were locally based. The implications for predisaster planning are discussed.